Variation of synovial fluid leucocyte cell count and polymorphonuclear percentage in patients with aseptic revision total knee arthroplasty. (2021) - Fuchs, M.; Kirchhoff, F.; Reichel, H.; Perka, C.; Faschingbauer, M.; Gwinner, C.
No abstract available